Worldwide pacemaker and defibrillator reuse: Systematic review and meta‐analysis of contemporary trials. Issue 11 (19th September 2018) - Sinha, Sunil K.; Sivasambu, Bhradeev; Yenokyan, Gayane; Crawford, Thomas C.; Chrispin, Jonathan; Eagle, Kim A.; Barth, Andreas S.; Rickard, John "Jack"; Spragg, David D.; Vlay, Stephen C.; Berger, Ronald; Love, Charles; et al.
Abstract: Background: Patients go without pacemaker, defibrillator, and cardiac resynchronization therapies (devices) each year due to the prohibitive costs of devices. Objective: We sought to examine data available from studies regarding contemporary risks of reused devices in comparison with new devices. Methods: We searched online indexing sites to identify recent studies. Peer‐reviewed manuscripts reporting infection, malfunction, premature battery depletion, and device‐related death with reused devices were included. The primary study outcome was the composite risk of infection, malfunction, premature battery depletion, and death. Secondary outcomes were the individual risks. Results: Nine observational studies (published 2009–2017) were identified totaling 2, 302 devices (2, 017 pacemakers, 285 defibrillators). Five controlled trials were included in meta‐analysis (2, 114 devices; 1, 258 new vs 856 reused). All device reuse protocols employed interrogation to confirm longevity and functionality, disinfectant therapy, and, usually, additional biocidal agents, packaging, and ethylene oxide gas sterilization. Demographic characteristics, indications for pacing, and median follow‐up were similar. There were no device‐related deaths reported and no statistically significant difference in risk between new versus reused devices for the primary outcome (2.23% vs 3.86% respectively, P = 0.807, odds ratio = 0.76). There were no significant differences seen in the secondary outcomes for the individual risks of infection, malfunction, and premature battery depletion. Conclusions: Device reuse utilizing modern protocols did not significantly increase risk of infection, malfunction, premature battery depletion, or device‐related death in observational studies. These data provide rationale for proceeding with a prospective multicenter noninferiority randomized control trial.